Open traceability tool for EUDR compliance through co-designed digital infrastructure adopted by Honduran coffee farmers - Ceballos Sierra, Federico (2025)
TraceFoodChain.org is an open-access traceability tool for EUDR compliance, developed by Permarobotics based on a digital infrastructure blueprint co-created with stakeholders of the Honduran coffee value chain. Facilitated by the Alliance, the three-month prototyping process defined key elements for interoperability, data ownership, and confidentiality. With a potential adoption by IHCAFE and ICF as a national standard, this blueprint could benefit up to 120,000 farmers and foster pre-competitive collaboration, enabling transparent and verifiable compliance with EUDR through integrated digital solutions.